Marketing Communication Collaboration Destination Marketing Organization: Analysis of Collaboration through Instagram Social Media the New Face of Taman Mini Indonesia Indah's Pavilions - Edith Santana (Budapest International Research and Critics University, 2024)
This study aims to provide suggestions in identifying and also providing information / views that are educational, cultural and also while recreating to the wider community both locally and internationally where with the theory of Destination Marketing Organization also collaboration on marketing communications related to the Taman Mini Indonesia Indah Wajah Baru tourist destination through Instagram social media analysis with the aim of being able to maintain a collaborative assessment of the development of the Taman Mini Indonesia Indah Wajah Baru tourist destination through the Pavilions - Pavilions from the uniqueness of each region that implements the latest philosophy, namely Inclosive, Green, Culture and Smart. Tourists can also enjoy seeing the beauty of Taman Mini Indonesia Indah Wajah Baru after revitalization and can be accessed via smart phones, Instagram social media. Tourist destinations are the largest sector. The main purpose of utilizing social media is to maintain good relations between companies and the public / wider community by establishing relationships to create communication in the aspect of information and interaction where the public's vision in collaborative conversations to provide mutually beneficial value. The basic concept of marketing also explains that tourist destinations, explain how Destination Marketing Organizations collaborate with stakeholders, local communities and businesses to create interesting narratives that are also in accordance with the target audience. Social media engagement, branding based on evolving experiences can highlight how Destination Marketing Organizations adapt to technological advances to reach a wider spectrum of travelers, as well as global tourist destinations. In short, so that Taman Mini Indonesia Indah Wajah Baru can provide a good image in the wider community.